2012
DOI: 10.1007/s00436-012-3035-2
|View full text |Cite
|
Sign up to set email alerts
|

Giardia intestinalis: effects of Pulsatilla chinensis extracts on trophozoites

Abstract: Pulsatilla chinensis is a medicinal root plant that has been used to treat a wide range of disease conditions. Our study determined the antiprotozoal activity of various P. chinensis extracts and fractions against Giardia intestinalis including their effects on parasite growth, cell viability, adherence, and morphology. Ethyl acetate extracts (IC50 = 257.081 μg/ml) were the most active to inhibit the growth of G. intestinalis followed by aqueous extract (PWE), saponins, and n-butanol extract. The PWE and ethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Based on acute and sub-chronic toxicity, Pulsatilla granules might be considered safe for veterinary use (Jia et al, 2017). Previous studies have also confirmed that the root of Radix Pulsatilla has potential therapeutic use against giardiasis (Li et al, 2012) and the possible prevention of infection (for example HBV) by specifically increasing SOD activity to minimize superoxidemediated toxicity and increase superoxide release in the liver (Yao et al, 2004). Although in vivo and in vitro researches have shown that PD exerts important pharmacological effects, only few have explored its effect against DHD based on the Chinese Traditional Medicine theory.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on acute and sub-chronic toxicity, Pulsatilla granules might be considered safe for veterinary use (Jia et al, 2017). Previous studies have also confirmed that the root of Radix Pulsatilla has potential therapeutic use against giardiasis (Li et al, 2012) and the possible prevention of infection (for example HBV) by specifically increasing SOD activity to minimize superoxidemediated toxicity and increase superoxide release in the liver (Yao et al, 2004). Although in vivo and in vitro researches have shown that PD exerts important pharmacological effects, only few have explored its effect against DHD based on the Chinese Traditional Medicine theory.…”
Section: Introductionmentioning
confidence: 96%
“…A solid theoretical and experimental foundation exist for the use of PD to treat DHD (Zhang et al, 2014). Pulsatilla chinensis (Bunge) Regel, which is listed in the Chinese Pharmacopeia, has been used to remove heat, expel miasma, and cool the blood to stop diarrhea (Li et al, 2012). For thousands of years, the dried bark of Phellodendron amurense Rup.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, one of the greatest challenges for public, rural, and medical health professionals involved in the control of giardiasis and other parasitic diseases is finding novel, safe, cost-effective drug alternatives. Recent studies have begun to re-examine the use of complementary and alternative therapies including plant extracts used in traditional healing systems, 11 essential oils, 12,13 and functional foods such as saturated fatty acid rich coconut milk 14 to treat giardiasis.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, osthole (10 mg/mL) impaired the ultrastructure of Giardia lamblia against its infection. Specifically, the impaired suction membrane led to the unstable suction and malnutrition for Giardia lamblia [146]. Imperatorin (LD 50 = 3.14 mg/L) and osthole (LD 50 = 13.11 mg/L) could be utilized as larvicides in the management of mosquito populations, especially to target insecticide-resistant mosquito larvae [147].…”
Section: Parasitic Diseasementioning
confidence: 99%
“…For another kind of parasite, Giardia lamblia, osthole may inflict a series of structure alterations which included cell membrane damage, nuclear deformity, and sucking structure damage. Therefore, it is reasonable to deduce that all these structure alterations induced abnormal physiological functions including unstable sucking and deteriorating nutrition absorption, which led to autophagy and death [146]. The most efficient concentration was 5.0 mg/mL in the study which could approximately reduce the number of the parasite down to 21.38% with IC 50 was 1.345 mg/mL, it also deactivated the vitality of the parasite down to less than 50% after 5 h intervention [149].…”
Section: Parasitic Diseasementioning
confidence: 99%